Renal Protective Effect of Resveratrol against Vincristine-Induced Oxidative Stress in Female Mice - Mohammadreza Nasirzadeh; Mir Hadi Khayatnouri; Saeed Taginasab; Pouya Navidi far; Mohammad Bakhshi; Heidar Tayefesattari (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Vincristine (VIN) is a broad-spectrum anticancer drug used to treat various cancers. Resveratrol (Res) is a natural polyphenol found in numerous plant sources. Many studies have reported anti-inflammatory and antioxidative effects of resveratrol. In this study, the effect of resveratrol on kidney damage caused by vincristine in female mice has been investigated. Methods: In this study, 36 female mice weighing 25-30 grams were randomly divided into four groups (n=9): 1) Control group, 2) Vin- group, 3) Vin-Res group and 4) Res group. The mice received vincristine at 3 mg/kg once a week for 4 weeks and resveratrol at 30 mg/kg daily for 28 days through gavage. At the end of the study, the fat peroxidation index (MDA), total antioxidant capacity (TAC), and the activities of the antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPX) in kidney tissue were measured. Data were presented as mean ± standard deviation, and the significant differences among groups were analyzed using SPSS16, one-way ANOVA, and Tukey's post hoc test. Results: The findings indicated that in the vincristine group, levels serum of urea, creatinine, and MDA in kidney tissue were increased significantly compared to the control group (P=0.001).the TAC level and the activity level of GPX (P=0.001) and SOD (P=0.009) enzymes in the kidney tissue were  significantly decreased in the vincristine group when compared to the control group (P=0.001). Conclusion: The results of this study showed that the protective effects of resveratrol were probably attributed to its antioxidant properties and that it could reduce the kidney damage induced by vincristine.